Laser ultrasound measurement of diaphragm thickness, Young’s modulus and Poisson’s ratio in a MEMS device - McKee, Campbell; Culshaw, Brian; Leach, Richard K. (Institute of Electrical and Electronics Engineers, 2016)
Laser-generated Lamb waves, coupled with a large bandwidth Michelson interferometer, have been demonstrated to accurately measure the thickness of a MEMS pressure sensor diaphragm in the [110] direction of a silicon wafer. Using the reassigned Gabor time-frequency method to produce group velocity dispersion curves, the technique facilitates the measurement of thickness, Young’s modulus and Poisson’s ratio from just one non-contact measurement. In this investigation, thickness was determined to be 35.01 μm ± 0.18 μm. For comparison, the thickness was measured using an independent optical technique; obtaining a value of 34.60 μm ± 0.27 μm. Values for Young’s modulus and Poisson’s ratio were also determined to be 163 GPa ± 11.7 GPa and 0.351 respectively and these are in good agreement with values found in the literature.